Prisoner of Tehran : a memoir - Nemat, Marina (New York : Free Press, 2007)
Nemat tells the heart-pounding story of her life as a young girl in Iran during the early days of Ayatollah Khomeini's brutal Islamic Revolution--arrested, tortured, and sentenced to death for'political crimes.'--From publisher description
Keywords: Nemat, Marina, -- 1965-; Women political prisoners -- Iran -- Biography; Political prisoners -- Iran -- Biography; Iran -- Politics and government -- 1979-1997